IMPLIKASI HUKUM TERHADAP PENARIKAN OBJEK JAMINAN FIDUSIA OLEH PERUSAHAAN LEASING SECARA MELAWAN HUKUM (Studi Putusan No. 973/Pdt.G/2015/PN Dps) - Laila Turrahmi; Benni Rusli (Ensiklopedia of Journal, 2023)
The researcher discusses the problem of Unlawful Actions in Forced Withdrawal of Fiduciary Guarantee Objects (Decision Study Number. 973/Pdt.G/2015/PN Dps) This is done to analyze the case against the implementation of the withdrawal of the fiduciary object by the defendant. This case originated with a credit agreement between the plaintiff and the defendant with the object of collateral in the form of an ISUSU Truck vehicle with the ELF Brand and bound by a fiduciary guarantee. The aim is to find out the unlawful act of withdrawing a fiduciary guarantee object and the form of the judge's consideration of the withdrawal of a fiduciary guarantee object that is carried out unlawfully. The form of research used by the authors is normative juridical, in normative juridical research the authors use literature as relevant secondary data, processing all data that has been obtained by the authors using descriptive data types, the data analysis method used is qualitative. So that from this research the results are obtained, namely the legal consequences of executing fiduciary guarantees that are not registered, the creditor is not legally executing the object of fiduciary guarantees directly, the execution process must be carried out by filing a civil suit to the District Court until a judge's decision has permanent legal force.